2022
DOI: 10.1002/fsn3.3136
|View full text |Cite
|
Sign up to set email alerts
|

Miao sour soup influences serum lipid via regulation of high‐fat diet‐induced intestinal flora in obese rats

Abstract: Obesity is associated with the gut microbiota and has been shown to cause gut microbiota disturbances. Our previous studies have demonstrated that Miao sour soup (SS) contains abundant short‐chain fatty acids (SCFAs) which can be used as energy substrates of intestinal flora to selectively stimulate their growth and reproduction. Therefore, we explored whether the intestinal microbiota of rats with high‐fat diet‐induced obesity could be restored to normal by SS intervention. Male obese rats were divided into f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Another is that differences in social support and lifestyle factors may also account for differences in the increased risk of hypertension between races/ethnicities (35,36). In addition, relevant studies have shown that the characteristic diet of ethnic minorities can reduce blood lipid levels and improve lipid metabolism disorders and the oxidative stress caused by obesity (37)(38)(39). Even so, due to the lack of research on visceral fat and hypertension in ethnic minorities in China, the relationship between the METS-VF and the risk of incident hypertension needs to be further investigated to examine the mechanisms involved in ethnic differences.…”
Section: Discussionmentioning
confidence: 99%
“…Another is that differences in social support and lifestyle factors may also account for differences in the increased risk of hypertension between races/ethnicities (35,36). In addition, relevant studies have shown that the characteristic diet of ethnic minorities can reduce blood lipid levels and improve lipid metabolism disorders and the oxidative stress caused by obesity (37)(38)(39). Even so, due to the lack of research on visceral fat and hypertension in ethnic minorities in China, the relationship between the METS-VF and the risk of incident hypertension needs to be further investigated to examine the mechanisms involved in ethnic differences.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the fermentation process of red sour soup will produce beneficial bacteria such as Lactobacilli, Acetobacter , and Leuconostoc and acid substances such as lactic acid, acetic acid and citric acid [ 38 ]. These acids regulate inflammation and promote immunity, neuroprotection, and anti-ageing activity [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it can rectify both IM dysbiosis induced by a high-fat diet and impairments in lipid metabolism and glucose tolerance (Jing et al, 2020). Miao sour soup lowers body weight and lipid levels, as well as levels of TNF-a and IL-6 in the intestinal mucosa while it elevates the levels of PYY and GLP-1 in the colonic tissues, and increases the expression of PYY and ZO-1 in the intestinal epithelial cells in obese rats (Zhou et al, 2023). Polygonatum kingianum regulates the abundance and diversity of the IM community by increasing the relative abundance of SCFA-producing bacteria.…”
Section: Regulation Of Glucose and Lipid Metabolismmentioning
confidence: 99%